Assessing the Kinta Riverwalk as a successful public space using the place diagram / Mohammad Nazrin Zainal Abidin ... [et al.] - Zainal Abidin, Mohammad Nazrin; Sayed Abul Khair, Sayed Muhammad Aiman; Anuar, Izzat; Abdul Hakeem Abas, Salahuddin; Hasbullah, Mohd Nasurudin (2022)
The Kinta Riverwalk in Perak has been promised by the state administration that it will not become a "white elephant" project. As specified in the RKK and Ipoh Walkable City and the Ipoh Local Plan 2035, planning for the Old Town Tourism Area will benefit from this development. However, to develop a fulfilling and functional public space, it is critical to understand the needs of space as well as the interaction between its users. Therefore, this study is aimed to assess the quality of the site as a successful public space. According to the Project for Public Space, successful public spaces share four characteristics: they are easily accessible, bustling with activity, welcoming and well-maintained, and sociable, allowing locals and visitors to meet and socialise. This study applies the Place Diagram by the Project for Public Space as a theoretical framework to assess the quality of the site. A digital form has been used via Google Form and distributed to 85 second-year architecture students. The questionnaires are divided into 4 sections; access and linkages, comfort, and image, uses and activities, and sociability. The data is analysed with a quantitative approach using SPSS (Statistical Package for the Social Sciences) v.28 on frequency analysis were to rank the variables. From the findings, the Kinta Riverwalk is a potential successful public space in Ipoh offering variety of uses and activities. Even though the uses and activities are the strongest variables that make the place highly potential, SPSS analysis shows that it needs to improve in terms of comfort and image. This can be amended by increasing public surveillance and offering more facilities to ensure that the public always feels safe. Furthermore, based on the results of this study, it is highly recommended that future researchers and professionals explore placemaking strategies using the Place Diagram.